Ministerial Decree No 381/2014 Concerning Tourist Buses = قرار وزاري رقم 381 لسنة 2014 بشأن الحافلات السياحية / Ministry of Tourism - Egypt. Ministry of Tourism (2025)
Decree no. 381 of the 2014 issued 27/4/2014 – قرار رقم 381 لسنة 2014 صادر بتاريخ 27/4/2014